First record of hard tick species, Hyalomma marginatum marginatum and H. marginatum rufipes (Acari: Ixodidae), as probable vectors of Crimean-Congo hemorrhagic fever virus, from the spur-thighed tortoise, Testudo graeca (Reptilia: Testudinidae), SE Iran - Moslem Adeli-Sardou; Kourosh Azizi; Aboozar Soltani; Mohammad Djaefar Moemenbellah-Fard (Persian Journal of Acarology)
Ticks (Acari: Ixodidae) are one of the most successful and widespread vectors of zoonotic pathogens of medical interest. Most ticks use a wide spectrum of vertebrate hosts, including tortoises. They are obligatory ectoparasitic blood sucking arthropods on egg laying (ovipositing) and/or mammalian hosts. The present investigation was part of a wider survey to study the fauna of wild ticks on primarily selective domesticated mammals and subsequently the likely tick infection with Crimean-Congo hemorrhagic fever (CCHF) virus RNA. Ticks were morphologically identified to species level using a valid regional taxonomic key. They were subsequently processed for the presence of CCHF virus RNA using reverse transcription polymerase chain reaction (RT-PCR). During this survey, two natural tortoises were found infested with ticks at highland. Hard tick species of Hyalomma marginatum marginatum, Hy. marginatum rufipes and Hy. marginatum aegyptium were found in attachment to two Eastern spur-thighed tortoise species of Testudo graeca (Reptilia: Testudinidae) for the first time in southeast Iran. These host tortoises were discovered at high altitude region of about 2800-2900m above sea level in the vicinity of a village in Jiroft county, Kerman province, Iran. None of these tortoise-associated ticks were infected with CCHF virus RNA. Since herd breeding nomads often climb to highland to improve animal grazing in open shrub land, the importance of infestation with wild ticks potentially infected with various pathogens is described.